DEVELOPMENT OF INTERACTIVE MEDIA BASED ON ARTICULATE STORYLINE IN FIQH SUBJECTS OF HAJJ AND UMRAH MATERIALS CLASS VIII MTSN 8 AGAM - Antoni, Antoni; Hadeli, Hadeli; Eliza, Rivdya (Jurnal Manajemen Pendidikan, 2025)
This research is motivated by the fact that the use of digital media that is not optimal and less varied such as when explaining lessons is only supported by youtube media without any editing, this is because teachers are often burdened with high administration and workload, so that they find it difficult to spend time learning and integrating digital media into the teaching process This research aims to To produce interactive media based on articulate storylines that are valid, practical and effective in fiqh subjects of Hajj and Umrah material class VIII MTsN Agam. The research uses the Four-D (Define, Design, Develop, Disseminate) model. The test subjects amounted to 23 students with interactive media objects based on articulate storyline. The results of the study show that the media developed is valid, very practical, and effective. Practicality from a student's perspective reached 92.87% (very practical category). Effectiveness was proven through a paired t-test between pretest–posttest with t-count = 9.27 > t-table = 2.074 (df = 22; α = 0.05), so that there is a significant difference in learning outcomes after using media. This finding confirms that the interactive media developed is feasible to support the achievement of fiqh learning goals in Hajj and Umrah materials at the MTsN 8 Agam level.